Slipped Capital Femoral Epiphysis (SCFE) - diagnosis and treatment - Magdalena Makarewicz; Magdalena Kubicka; Joanna Wilk; Paweł Dębiec; Krystian Cholewa; Adrianna Szymańska (Kazimierz Wielki University, 2023)
Background Slipped Capital Femoral Epiphysis is the most common pathology of the hip joint in preschool children and adolescents consisting of migration of the proximal femoral epiphysis, posteriorly and inferiorly, to the metaphysis (neck of the femur), which occurs through the epiphyseal (growth) cartilage. SCFE occurs with a frequency of 0.33 per 100,000 to 24.58 per 100,000 children aged 8-15 years. Purpouse The aim of the article is to characterize the disease which is SCFE, draw attention to its etiology, diagnostic and therapeutic possibilities. Materials and methods The article was based on scientific publications in the Pubmed database. The database was searched on 12 February 2023 using the phrases 'SCFE', 'Slipped Capital Femoral Epiphysis'. After reading the titles of found articles, 23 publications were selected. After the pre-analysis of the abstracts, 15 full-text works were selected to prepare the article. Results Most SCFE is idiopathic. The relationship between the development of SCFE and endocrine disorders, renal dysfunction and Down syndrome has been noted. The displacement is presumed to be caused by the application of a large axial load to the relatively fragile growth plate. Symptoms of the disease may include atraumatic pain in the hip, thigh or knee, especially if accompanied by a limp or inability to support weight. The first imaging test performed is a radiograph. If radiographs do not show changes consistent with SCFE but clinical suspicion is high, the physician may consider magnetic resonance imaging (MRI) for further evaluation. The goal of treating the lesions is to prevent further scaling of the head and to correct the deformity and to avoid osteonecrosis and chondrolysis, so various surgical procedures are used. Conclusions SCFE is an insidious disease that should always be ruled out in the diagnosis of hip pain in children. Its early treatment prevents later complications.